Comparison of The Analgesic Efficacy of Genicular Nerve Phenol Neurolysis In Patients with Knee Osteoarthritis Versus Radiofrequency Ablation - Hayat, Muhammad Umer; Iqbal, Mudassar; Waseem, Syed Majid; Saqib, Usman; Tariq, Kiran; Qadri, Muhammad Hisaan Anjum (Pakistan Armed Forces Medical Journal, 2026)
Objective: To compare the analgesic efficacy of genicular nerve phenol neurolysis compared to radiofrequency ablation in patients with knee osteoarthritis. Study Design: Quasi-experimental study. Place and Duration of Study: Department of Pain Management, Combined Military Hospital (CMH), Rawalpindi, Pakistan, from Feb to Jul 2025. Methodology: A total of 154 patients were recruited into the study and divided into two groups: Group PN using phenol neurolysis (n=77) and Group RA using radiofrequency ablation (n=77). Patients with Grade III or IV osteoarthritis, moderate to severe knee pain, persistent pain >6 months or failure of conservative treatment were included. Pain score on Numerical Rating Scale (NRS) and Western Ontario and McMaster Universities Arthritis Index (WOMAC) scale at baseline, 2, 4 and 12 weeks were recorded. Results: Participants had a median age of 60 (58.00-63.00) years and a Body Mass Index (BMI) of 28 (27.00-30.00) kg/m2. Intragroup median pain score and WOMAC score interpretation revealed significant improvement from baseline in both groups (p <0.001). At 12 weeks median pain score was 3.33 (3.23-3.60) in Group PN as compared to 3.13 (2.00-3.33) in Group RA (p <0.001). Functional status assessment on WOMAC scale at 12 weeks revealed a higher median score of 37.40 (36.35-39.80) in Group PN as compared to 37.20 (34.75-38.30) in Group RA, with a p-value of 0.026. Conclusion: Radiofrequency ablation appears to be superior at 12 weeks as compared to genicular nerve phenol neurolysis in providing pain relief and improvement of functional status in patients with knee osteoarthritis.